GROWTH RESPONSE OF OIL PALM SEEDLINGS (Elaeis guineensis Jacq.) TO THE SUPPLY OF SWIFTLET DROPPINGS BOKASHI AND RAINBOW NPK FERTILIZER: RESPON PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) TERHADAP PEMBERIAN BOKASHI KOTORAN WALET DAN PUPUK NPK PELANGI - Purwati Purwati; Indra Lesmana (Agrifarm : Jurnal Ilmu Pertanian, 2025)
The purpose of this study was to determine the response of oil palm seedling growth to the provision of Bokashi Swiftlet Droppings in the planting medium and Rainbow NPK fertilizer and the interaction of the two treatments. The study was conducted for 4 months, starting from March 2025 preparation to June 2025 the last data collection and took place at the Research Field of the Faculty of Agriculture, Widya Gama Mahakam University Samarinda, Jalan Wahid Hasyim, Sempaja Village, North Samarinda District, East Kalimantan. The research method used a Factorial Randomized Block Design (RAK) consisting of 2 factors with 3 replications. The first factor is Bokashi Swiftlet Droppings (B) which consists of 3 levels, namely: B0 (Control), B1 (500 g/polybag), and B2 (1,000 g/polybag). The second factor is Rainbow NPK Fertilizer (N) which consists of 4 levels, namely: N0 (Control), N1 (10 g/polybag), N2 (20 g/polybag), and N3 (30 g/polybag). The observation variables are plant height growth, stem diameter and number of leaves. The results showed that Bokashi Swiftlet Droppings gave significant results on all parameters of 90 HSP age with the best dose of 1,000 g/polybag. Rainbow NPK Fertilizer gave significant results on all parameters of 60 and 90 HSP age with a dose of 30 g/polybag. While the interaction between Bokashi Swiftlet Droppings and Rainbow NPK did not have a significant effect on all parameters observed.